2017
DOI: 10.1007/s11628-017-0341-x
|View full text |Cite
|
Sign up to set email alerts
|

A model of collaborative innovation between local government and tourism operators

Abstract: This research proposes a framework for collaborative innovation in a public private partnership by applying techniques that combine quantitative data collection and qualitative depth. It proposes a collaborative model that looks to provide competitive advantage by improving tourist services from two perspectives: from the core of public administration, and from the private tourist sector perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is an important index to measure the development trend of the discipline and is of great significance to analyze the development trend and future trend of the research field. Through the annual statistics of the selected literature [5], literature [8], literature [9], and literature [10], it can be seen that there are some differences in the time evolution of the number of papers on tourism economic benefits at home and abroad, but on the whole, they all show the development trend of "first stable, then increasing, and then natural decline". Three experiments were carried out, respectively, and the experimental results are shown in Figures 3, 4, and 5.…”
Section: Experimental Results Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an important index to measure the development trend of the discipline and is of great significance to analyze the development trend and future trend of the research field. Through the annual statistics of the selected literature [5], literature [8], literature [9], and literature [10], it can be seen that there are some differences in the time evolution of the number of papers on tourism economic benefits at home and abroad, but on the whole, they all show the development trend of "first stable, then increasing, and then natural decline". Three experiments were carried out, respectively, and the experimental results are shown in Figures 3, 4, and 5.…”
Section: Experimental Results Andmentioning
confidence: 99%
“…At present, China's economic development has entered the new normal, and the previous extensive and expanded economic growth mode has been unsustainable. It is urgent to create a new development engine driven by innovation and promote economic development to a new track characterized by intensive and quality [4,5]. Innovation driven development strategy is the internal requirement of transforming China's economic development mode, and a strategic deployment to meet the challenges of international competition and seek national leapfrog development.…”
Section: Introductionmentioning
confidence: 99%
“…Mutual communication flows provide quality to project management, particularly concerning the setting of objectives and monitoring progress. This implies fluency, flexibility, simplification and transparency in procedures (Draghici et al, 2017; Pons-Morera et al, 2018). As part of formal incubation or acceleration processes, programmes like business incubators or accelerators supported by major companies, such as SIA’s KrisLab, JetBlue Technology Ventures, Hangar 51 supported by IAG Group, Boeing HorizonX Ventures and Aviation X Lab by Emirates Airline, offer continuous communication with the teams involved, providing mentoring programmes with top executive boards, periodic meetings, progress checkpoints and follow-ups during the period of incubation or acceleration.…”
Section: Key Factors Framework Cases and Resultsmentioning
confidence: 99%
“…The collaboration between stakeholders in the tourism sector shows a mutually beneficial relationship. A previous study found that collaboration between local government and the tourism industry could increase the number of tourist visits and the quality of tourism business services [22]. Furthermore, it was emphasized that the mutually beneficial collaboration between the tourism industry and local government might improve the community's economy through the income from tourist spending when visiting [23].…”
Section: Introduction mentioning
confidence: 99%